2006
DOI: 10.1258/000456306778904713
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Bayer Advia Centaur® immunoassay results obtained on samples collected in four different Becton Dickinson Vacutainer® tubes

Abstract: Addresses

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…However, Giavarina et al (11) found that lithium heparin plasma could not be used for analysis of folate, testosterone, vitamin B12, and progesterone with the Siemens Advia Centaur ᭨ analyzer (Siemens Healthcare Diagnostics, Medfield, MA, USA). These findings were in agreement with findings reported by Morovat et al (18).…”
Section: Introductionsupporting
confidence: 94%
“…However, Giavarina et al (11) found that lithium heparin plasma could not be used for analysis of folate, testosterone, vitamin B12, and progesterone with the Siemens Advia Centaur ᭨ analyzer (Siemens Healthcare Diagnostics, Medfield, MA, USA). These findings were in agreement with findings reported by Morovat et al (18).…”
Section: Introductionsupporting
confidence: 94%
“…The use of specialized serum tubes can reduce the required clotting time required and formation of fibrin. During the analytical phase there are additional limitations on the analytical method and the type of tests that can be performed, defined by the compatibility between the analyte and the sample additive, most notably those used for immunoassays (42). Finally, maintaining the sample stability during extended storage is of great benefit to the laboratory, particularly for 'add-on' or future testing.…”
Section: Usefulness Of Primary Sample Collection Systems In Reducing mentioning
confidence: 99%
“…Smets et al compared plastic and glass evacuated serum separator tubes and did not find a major difference between SST glass and plastic for estradiol and testosterone [14]. Bush et al [15] and Morovat et al [6] also reported that the storage of serum within the gel containing tube may cause a decrease in the measured estradiol and testosterone. Decrement in the results of estradiol and testosterone in both gel separator tubes might be due to absorbtion of gel similiar to the same mechanism effecting the therapeutic drug analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant differences in many routine biochemical analysis have not been seen, many articles have been published reporting significant declines especially in therapeutic drug levels [3,4]. Recently, published articles have reported the significant effects of gel separator tubes on total triiodothyronine [5] and vitamin B12 [6] immunoassays.…”
Section: Introductionmentioning
confidence: 99%